TINJAUAN HUKUM TERHADAP KASUS TINDAK PIDANA PEMERASAN OLEH OKNUM POLISI BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA - Firman Selvian Rosady (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            This study examines how the regulation of extortion under the Penal Code (KUHP) and Law No. 2 of 2002 on the Law of the Republic of Indonesia.            This research is scientific research to find out the truth based on scientific logic from the legal side by using laws and regulations. The types of legal entities that the author uses are primary legal materials, secondary legal materials, as well as tertiary legal materials.            The formulation of the Criminal Code does not provide room at all against the implementation of extortion measures. The regulation is regulated in Article 13 letter b and c, Article 14 paragraph 1 of Law Number 2 the Year 2002. And in Government Regulation Number 2 the Year 2003 namely Article 3 letter c, Article 3 letter f, Article 3 letter g, Article 4 letter c and d, Article 4 letter f, Article 4 letter h, Article 4 letter I, Article 4 letter j, Article 5 letter a and Article 6 letter q.            The imposition of disciplinary sanctions against police officers can not eliminate criminal sanctions because it has committed extortion as contained in Article 368 paragraph 1 of the Criminal Code. Keywords: Extortion, disciplinary sanctions can not impose criminal sanctions.